Distribution of neuropeptide Y immunoreactive nerve fibers and cells in Alligator's heart - ZHANG Jia-xing; HUANG Xue-ying; HE Juan-juan; JIANG Jia-yuan (浙江大学学报. 农业与生命科学版, 2001)
Immunohistochemical (ABC) and FITC-coupled indirect immunofluoresence methods were used to reveal NPY-IR fibers and cells in Alligator's heart. The result show that NPY-IR fibers and cells were mainly distributed in ventricle and the venous sinus, with less distribution in the atrium and the aortic valve. The IR fibers were characterized in general of beaded shape or of thread appearance and most commonly in the myocardium and cpicardium. All these implied that Alligator a typical amphibia animal, possesses NPY in the heart and thus has peptidergic nerve, which furthers the understanding of the comparative anatomy as well as provides new evidence of the functions of NPY in the cardiovascular system.